Communication between oncologists and lymphoma survivors during follow-up consultations: A qualitative analysis. Issue 5 (3rd September 2017) - Franco, Kara; Shuk, Elyse; Philip, Errol; Blanch-Hartigan, Danielle; Parker, Patricia A.; Matasar, Matthew; Horwitz, Steven; Kissane, David; Banerjee, Smita C.; Bylund, Carma L.
ABSTRACT: Cancer survivors often experience both short- and long-term challenges as a result of their cancer treatment. Many patients report feeling "lost in transition" following cancer treatment. The oncologist plays a key role in helping the patient to transition to survivorship. The purpose of this paper is to provide a descriptive understanding of the clinical care delivered during follow-up visits for lymphoma patients transitioning from active therapy into survivorship. We used thematic text analysis to identify themes in transcripts of audio recordings of 21 physicians and their patients in follow-up visits within 3 years of completing lymphoma treatment. Conversations between oncologists and patients during follow-up visits addressed a variety of themes, including specific health concerns, follow-up care, health promotion, prior treatment and test results, overall health status, emotional communication and affective tone, post-treatment rehabilitation, discussions occurring in the patient's physical examination, and social issues. However, the frequency with which these themes were discussed varied. In addition, there did not appear to be a consistent framework for these visits. The varied nature of the follow-up visits analyzed in this study suggests the need for increased structure in survivorship-care consultations.